Reasons for reoperation of patients undergoing surgical evacuation of an acute subdural hematoma – case raport and review of literature - Czyżewski, Wojciech; Stępień, Jakub; Tyzo, Bartłomiej; Litak, Jakub; Kulesza, Bartłomiej; Szmygin, Paweł; Staniewicz, Dominik; Torres, Kamil (Journal of Education, Health and Sport, 2019)
Background: We are presenting a case and as well as its analyzis regarding subdural hematoma reoperations.Case description: A 48-year-old patient after head trauma operated on due to diagnosed right-sided subdural hematoma. On the second day of hospitalization he developed epidural hematoma at the operation site, which reuired second surgery.Conclusion:Early detection and prompt treatment may improve the poor outcome in this group of patients.The choice between craniotomy and craniectomy and additional risk factors as ASA and antiplatelet intake as well as age and alcohol abuse have unverified importance in the context of reoperation.